2019
DOI: 10.17219/acem/94140
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the remineralizing potential of dental restorative materials by analyzing their fluoride release profiles

Abstract: Background. The accessibility of the remineralizing ions in teeth's environment is essential for their incorporation into caries-affected dentin. Novel bioglass-reinforced materials capable of releasing fluoride, calcium and phosphates may be particularly useful in the tissue remineralization process. A novel restorative material, ACTIVA BioActive-Restorative (Pulpdent Corp., Watertown, USA), is a hydrophilic resin-modified glassionomer cement (RMGIC) enriched with bioglass particles and fortified with a paten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
(34 reference statements)
3
23
0
1
Order By: Relevance
“…ACTIVA BioACTIVE-BASE/LINER (Pulpdent, USA) was launched in 2014 claiming the strength, aesthetics and physical properties of composites and increased release and recharge of calcium, phosphate and fluoride in comparison with glassionomer (GI). On the other hand, it has been proven that the fluoride ion release of ACTIVA is lower than that of the conventional GI (Keta Molar Quick Aplicap, 3M ESPE, Saint Paul, MN, USA) and also than that of RMGI cement (VitremerTM, 3M-ESPE, Saint Paul, MN, USA) [130,131]. The results indicate the ACTIVA BioACTIVE does uptake fluoride and re-release it, which could offer decreased incidence of secondary caries.…”
Section: Activa Bioactivementioning
confidence: 99%
“…ACTIVA BioACTIVE-BASE/LINER (Pulpdent, USA) was launched in 2014 claiming the strength, aesthetics and physical properties of composites and increased release and recharge of calcium, phosphate and fluoride in comparison with glassionomer (GI). On the other hand, it has been proven that the fluoride ion release of ACTIVA is lower than that of the conventional GI (Keta Molar Quick Aplicap, 3M ESPE, Saint Paul, MN, USA) and also than that of RMGI cement (VitremerTM, 3M-ESPE, Saint Paul, MN, USA) [130,131]. The results indicate the ACTIVA BioACTIVE does uptake fluoride and re-release it, which could offer decreased incidence of secondary caries.…”
Section: Activa Bioactivementioning
confidence: 99%
“…However, the pore density was much lower than observed within a reference glass ionomer material. 15 The water sorption of Activa Bioactive Restorative was also about half that of a reference RMGI material. 16 THE is a self-adhesive resin cement with calcium silicate additives.…”
Section: Discussionmentioning
confidence: 93%
“…8 Most studies have reported significantly less fluoride released from this material than reference glass ionomer or RMGI materials. [13][14][15][16][17] A recent article stated that Bioactive Restorative. However, the pore density was much lower than observed within a reference glass ionomer material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations